Guidelines on prevention of preterm birth. (12th December 2022) - Munim, Shama; Islam, Zaheena; Zohra, Nishat; Yasmin, Haleema; Korejo, Razia
Abstract: This guideline has been prepared by the National Maternal Fetal Medicine guidelines committee and approved by the Society of Obstetricians and Gynecologists Pakistan. These recommendations will enable the practicing clinicians to optimally manage pregnancies at risk of preterm birth.